Cryptosporidiosis and Microsporidiosis in Ugandan Children with Persistent Diarrhea with and Without Concurrent - Bakeera-kitaka, Sabrina; Tumwiine, James K.; Ketiniinwa, Addy; Ndeezi, Grace; Downning, Robert; Xiaochun, Feng; Akioshi, Donna K.; Tzipori, Saul (The American Society of Tropical Medicine and Hygiene, 2005)
Cryptosporidium spp. and Enterocytozoon bieneusi are enteric pathogens that have emerged as significant causes of persistent diarrhea (PD) in immunologically compromised individuals particularly in association with HIV/ AIDS. We conducted a cross-sectional study on the clinical epidemiology of E. bieneusi and Cryptosporidium in children with PD, with and without HIV/AIDS, attending Uganda’s Mulago National Referral Hospital. Two hundred forty-three children aged < 60 months, admitted between November 2002 and May 2003 with PD (> 14 days), were analyzed for HIV status and CD4 lymphocyte counts, and stools were screened for the presence ofE. bieneusi and Cryptosporidium by microscopy and positive samples genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Eighty (32.9%) of the children were excreting E. bieneusi, and 76 (31.3%) were excreting Cryptosporidium. Ninety-one of the 243 children had HIV, of who 70 (76.9%) had E. bieneusi, versus 10 (6.6%) of the 152 without (odds ratio 47.33; 95% CI 19.88 to 115.97), while 67 (73.6%) had Cryptosporidium, versus 9 (5.9%) without (odds ratio 44.36; 95% CI 18.39 to 110.40). Children with counts < 25% CD4 cells were more likely to have either E. bieneusi (odds ratio 7.42; 95% CI 3.77 to 14.69) or Cryptosporidium (odds ratio 6.45; 95% CI 3.28 to 12.76) than those with higher CD4 percentages. However, only HIV status was independently associated with either Cryptosporidium or E. bieneusi. Among the 243 children with PD, 67 (27.8%) were infected with both enteric pathogens, with HIV being the only independent predictor of coinfection. Finally, some 81% of HIV-infected children with PD excreted one or both organisms, compared with only 10% of children with PD testing negative for HIV. Seventy-four percent of isolates were C. hominis, the anthroponotic species, 17% were C. parvum, the zoonotic species, and 8% were a mixture of the two or others.
Keywords: Crysptosporidiosis; Microsporidiosis; Persistent diarrhea; Human Immuno Deficiency Virus (HIV)